The Management of Orthostatic Hypotension in Parkinson’s Disease - Sanchez-Ferro, Alvaro; Benito-León, Julián; Gomez-Esteban, Juan Carlos (Frontiers in Neurology, 2013)
Orthostatic hypotension (OH) is a common and disabling symptom affecting Parkinson’s disease (PD) patients. We present the effect of the different therapies commonly used to manage PD on this clinical manifestation. For this purpose, we describe the relationship between OH and the current treatments employed in PD, such as L-DOPA, dopaminergic agonists, and continuous dopaminergic stimulation therapies. Additionally, we review the therapeutic measures that could be used to ameliorate OH. There are different approaches to deal with this manifestation, including pharmacological and non-pharmacological treatments, although none of them is specifically aimed for treating OH in PD.